Controlled turbulence regime of electron cyclotron resonance ion source for improved multicharged ion performance. (6th July 2021) - Skalyga, V A; Izotov, I V; Shalashov, A G; Gospodchikov, E D; Kiseleva, E M; Tarvainen, O; Koivisto, H; Toivanen, V
Abstract: Fundamental studies of excitation and non-linear evolution of kinetic instabilities of strongly nonequlibrium plasmas confined in open magnetic traps suggest new opportunities for development of electron cyclotron resonance (ECR) ion sources. These devices are widely used for the production of particle beams of high charge state ions. Operating the ion source in controlled turbulence regime allows increasing the absorbed power density and therefore the volumetric plasma energy content in the dense part of the discharge surrounded by the ECR surface, which leads to enhanced beam currents of high charge state ions. We report experiments at the ECR ion source at the JYFL accelerator laboratory, in which adopting of a new approach allows to increase the multicharged ion beam current up to two times, e.g. to 95 µ A of O 7 + achieved with mere 280 W power at 11.56 GHz. A theoretical model supporting and explaining the experimental findings is presented. The study suggests that the controlled turbulence regime has the potential to enhance the beam currents of modern high-performance ion sources, including state-of-the-art superconducting devices.